Pesan Dakwah dalam Film Rentang Kisah (Analisis Semiotika Roland Barthes) - Harahap, Reza Ramadhani; Hendra, Tomi (Institut Agama Islam Negeri Kerinci, 2022)
Da'wah is an exertion to construct the conditions that can help conversion the chaging of thoughts, beliefs, attitudes, and Islamic behaviors. Basicly da'wah is approved in mosques, as well as in public places by gathering societies as is mad'u, but similarly in modern era like today, da'wah has used complexity technologyy, one of them is film. The series film with a biographical drama genre, but it covers the meaning of da'wah messages, such as messages of aqidah, sharia and morals. This paper tries to expose the message of da'wah by using the semiotic approach of Roland Barthes.